Risk Factors of Coronary Heart Disease among Civil Employees of a Tertiary Level Hospital (Anwer Khan Modern Medical College Journal, 2020)
Background: Cardiovascular risk factors are the most inimical and deleterious elements to develop coronary heart disease (CHD). To identify the factors contributing to develop CHD is therefore of paramount importance. It needs endless attention to address the riddle. This effort is to candle the light on sociodemographic & other factors of CHD.Methods & Materials: This cross-sectional study was conducted in CMH Dhaka from September to December 2011 on 287 respondents. Data were collected by interview using semi-structured questionnaire. Data were checked, edited, coded, categorized, cleaned and analyzed using (SPSS version 20).Results: The study disclosed that respondent's mean age was 39.40+9.42 years, 67.2% were male and 32.8% were female. It was founded that 34.14% were smoker. The prevalence rate of HTN and DM were 14.3% and 4.5% respectably. The mean BMI was 24.55 with 58.5% had normal weight and 41.5% were overweight, 18.8% had positive family history of suffering from CHD. among the respondents 88.5% has got at least one risk factor, 60% has got 5-10 risk factors, 13.6% got 6-10 risk factors, 14.3% got>10 risk factors. Age was significantly associated with smoking (p